New Trends in Italian Cinema : ""New"" Neorealism. - Scala, Carmela Bernardetta (Cambridge Scholars Publishing, 2013)
Is the legacy of the Neorealist film-making mode (or should we say mood?) a withered one? If not, what is the ideal dialogue between contemporary Italian directors and this momentous page of their cultural history all about? The aim of this book is to show that, far from being exhausted, the vivifying lymph of post-Second World War Italian Neorealism continues to sustain the aesthetic praxis of many artists. Predominantly, the staying power of Neorealism becomes apparent in the stringent mor ...